SAE Technical Paper Series 2006
DOI: 10.4271/2006-01-2430
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation NASA GA Advanced Concept

Abstract: Not only is the common dream of frequent personal flight travel going unfulfilled, the current generation of General Aviation (GA) is facing tremendous challenges that threaten to relegate the Single Engine Piston (SEP) aircraft market to a footnote in the history of U.S. aviation. A case is made that this crisis stems from a generally low utility coupled to a high cost that makes the SEP aircraft of relatively low transportation value and beyond the means of many. The roots of this low value are examined in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, no small GA aircraft in series production features ducted fan propulsion due, in part, to its adverse effect on efficiency, as well as nacelle integration problems. More recently, several new projects have been and are being pursued in this field [4,19,22], among them the Airbus E-Fan [27] and the Silent Air Taxi [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, no small GA aircraft in series production features ducted fan propulsion due, in part, to its adverse effect on efficiency, as well as nacelle integration problems. More recently, several new projects have been and are being pursued in this field [4,19,22], among them the Airbus E-Fan [27] and the Silent Air Taxi [16].…”
Section: Introductionmentioning
confidence: 99%
“…These factors play a vital role in determining the preferred mode of transportation through their trade-offs. As suggested by Hahn, the demand for travel is often constrained by the time budget while the choice of travel mode is regularly dictated by the traveler's financial budget [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some people are mainly concerned on how much they have to pay for the transportation regardless of the time taken to travel while others may think the opposite. It has been suggested that travel demand is typically constrained by the time budget while the choice of travel mode is frequently dictated by the traveler's financial budget (Hahn, 2006).…”
Section: Introductionmentioning
confidence: 99%